1972
DOI: 10.1289/ehp.72025
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of noise and ototoxic drugs.

Abstract: Images FIGURE 1. FIGURE 4. FIGURE 5. FIGURE 6. FIGURE 8. FIGURE 9. FIGURE 10. FIGURE 11. FIGURE 12. FIGURE 14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

1977
1977
2003
2003

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 59 publications
0
7
0
2
Order By: Relevance
“…Noise has also been implicated as causal of hearing loss, especially in patients concomitantly receiving ototoxic drugs such as aminoglycosides. 13,14 Additionally, noise has been implicated in contributing to critical care nurse burnout. 15 The purpose of the current study was to determine the causes of noise pollution in the hospital setting and to determine if behavior modification could have an impact on noise in the ICU.…”
Section: P Revious Investigations At Our Institution Havementioning
confidence: 99%
“…Noise has also been implicated as causal of hearing loss, especially in patients concomitantly receiving ototoxic drugs such as aminoglycosides. 13,14 Additionally, noise has been implicated in contributing to critical care nurse burnout. 15 The purpose of the current study was to determine the causes of noise pollution in the hospital setting and to determine if behavior modification could have an impact on noise in the ICU.…”
Section: P Revious Investigations At Our Institution Havementioning
confidence: 99%
“…Long et al [4] noticed changes in oxygenation and intracerebral pressure accompanying noise bursts and Gadeke et al [7] observed infant sleep disturbances: these observations are important, because sudden changes in intracerebral perfusion may lead to cerebral haemorrhage [8] and disturbances in sleep cycles due to noise may provoke abnormal hormone production [9]. Loud or prolonged sounds can produce hearing loss in the frequency range of the damaging sound [10]: speech for example, is a low-frequency sound and hearing damage in this range has an enormous impact on language development and communication [3].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency spectrum of the acoustic exposure determines the location of maximum damage to the organ of Corti, whereas its intensity and duration control the severity of damage (Davis et al, 1953;Stockwell et al, 1969;Falk, 1972). In our previous study, the damage from tonal stimulation similar to that of the present experiment (i.e., 95 dB SPL tone at 2 kHz) but used for a longer period was characterized by cell damage limited to the second turn, i.e., to the segments 7 to 11 mm from the apex , and it affected outer as well as inner hair cells.…”
Section: Discussionmentioning
confidence: 99%